(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
In most literary works, especially in children’s literature, Roald Dahl is well-known for blending fantasy with realism. This article examines how Dahl creates an appealing storyline by contrasting fantastical and unbelievable events with real-life situations, characters, and societal issues. By utilizing a literary analysis, this research paper categorizes and differentiates realism and fantasy in a few of the author’s works, including Charlie and the Chocolate Factory, The BFG, and Matilda. According to the findings, Dahl employed the tool of realism to make his novels in a recognizable setting, whereas fantasy was intended to motivate readers and tackle crucial global issues.